Investigation of the properties of the amoeboid cell, a new cell type in oral cancer. (23rd February 2017) - Vig, Navin; Rahman, Muhammad; Gammon, Luke; Peyric, Elodie; Mackenzie, Ian
Abstract: Background: Cancer cell plasticity, as seen in epithelial-to-mesenchymal transition, can lead to metastasis and therapeutic failure. Another cell type, the amoeboid, has now been isolated in oral cancer. Previously seen in, but not isolated from melanomas and sarcomas, it has been associated with poorer prognosis. The aim of the study was to investigate the role of the amoeboid cell in oral cancer, with the hypothesis that it is a plastic, but more invasive and chemoresistant, cell type. Methods: In this in-vitro study of oral cancer cell lines (n=6), fresh tumour specimens, and mice, we used high-throughput invasion assays, migration and drug response assays, protein and gene expression profiling, mechanistic and pathway analysis, fluorescence-activated cell sorting, gene knockdowns, and immunostaining. At least three cell lines were used for each laboratory technique, with a minimum of triplicate repeats and appropriate statistical analysis. Findings: In all cell lines, amoeboid cells were smaller than both epithelial and mesenchymal cells (median cell area 295 μm 2 [IQR 218–399] vs 884 [573–1281] vs 598 [413–815]) but were significantly more migratory with a mean velocity of 1·1 μm/min (SD 0·2) versus 0·16 (0·08) for mesenchymal cells (p<0·0001). Amoeboid cells were four to 20 times more invasive than other cell types (p<0·0001). Greater chemoresistance was demonstrated against common agents including paclitaxel and etoposide. Gene analysis produced signatures associated with angiogenesis, anti-apoptosis, and invasion. Stemness genes were upregulated. Plasticity between phenotypes was clearly seen. Interpretation: We describe a new amoeboid cell phenotype, which is derived from epithelial cancer cells, that might confer upon carcinomas a greater ability to invade, disseminate, and resist therapy. A switch to an amoeboid phenotype could be a useful escape strategy for cancers, providing them with alternative modes for migration and invasion. However, this cell type essentially lacks keratin, which could complicate histopathological assessment of tumour spread. Pathway elucidation might yield new potential amoeboid targets. Targeting amoeboid cells, which may now become possible with their isolation and analysis, could be essential to improve patient outcomes. Funding: Royal College of Surgeons of England, British Association of Oral and Maxillofacial Surgeons, Facial Surgery Research Foundation, Faculty of Dental Surgeons (Royal College of Surgeons of England).